PROPOSAL OF PRIORITY AREAS INTERCONNECTING CONSERVATION UNITS IN ALTO IGUAÇU – PR - Da Silva, Ana Carolina; Galvão, Franklin; Accioly, Pyramon (Ra’e Ga: o Espaço Geográfico em Análise, 2023)
In Paraná, the Alto Iguacu basin is listed as one of the most important regions of the south of Brazil for water supply, in addition to the presence of several Conservation Units of different categories to protect the biodiversity of fauna and flora in the Atlantic Forest. This study aims to indicate relevant areas for the creation of ecological corridors in the Alto Iguaçu Basin using a GIS multi-criteria methodology, evaluating the plant typology, land use, and soil characteristics, and the diverse environments with the Phyto-environmental Units (UFAs) project. Tree areas were proposed to interconnect the protected areas covering the Mixed Rain Forest, Dense Rain Forest, and steppes, guaranteeing the representativeness of all Phyto-physiognomies present in the basin.